Multiscale Modeling of Vascular Remodeling Induced by Wall Shear Stress - Chen, Shiliang; Zhang, Hanbing; Hou, Qianwen; Zhang, Yu; Qiao, Aike (Frontiers in Physiology, 2022)
Objective: Hemodynamics induced low wall shear stress (WSS) is one of the critical reasons leading to vascular remodeling. However, the coupling effects of WSS and cellular kinetics has not been clearly modeled. The aim of this study is to establish a multiscale modelling approach to reveal the vascular remodeling behavior under the interaction between the macro scale of WSS loading and the micro scale of cell evolution. Method: Computational fluid dynamics (CFD) method and agent-based model (ABM), which have significantly different characteristics in temporal and spatial scales, were adopted to establish the multiscale model. The CFD method is for second/organ scale and the ABM is for month/cell scale. The CFD method was used to simulate blood flow in a vessel and obtain the WSS in a vessel cross section. The simulations of smooth muscle cell proliferation/apoptosis and extracellular matrix generation/degradation in a vessel cross sections were performed by using ABM. During simulation of vascular remodeling procedure, the damage index of smooth muscle cell and extracellular matrix was defined as deviation from the obtained WSS. The damage index decreased gradually to mimic the recovery of WSS induced vessel damage. Results: (1) The significant wall thickening region was consistent with the low WSS region. (2) There was no evident change of wall thickness in normal WSS region. (3) When the damage index approached to 0, the amount and distribution of smooth muscle cell and extracellular matrix achieved a stable state and the vessel reached the vascular homeostasis. Conclusions: The established multiscale model can be used to simulate the vascular remodeling behavior over time under various WSS conditions.